Primary tuberculous abscess of chest wall in a young immunocompetent female (Indian Journal of Case Reports, 2018)
Chest wall tuberculosis (TB) is rarely reported in immunocompetent individuals and is usually a part of disseminated disease. A tuberculous abscess may mimic pyogenic abscess and unless strongly suspected, tuberculous etiology may be missed due to paucibacillary nature of extrapulmonary lesions. Molecular diagnostic tests can prove useful by providing a rapid and accurate diagnosis in such cases. We present here a case of chest wall tuberculous abscess without any evidence of immunosuppression or previous history of TB.